Continuous 24 hour intraocular pressure monitoring for glaucoma with a contact lens sensor – time for a paradigm change (Swiss Medical Weekly, 2012)
Glaucoma is the main cause of irreversible blindness and intraocular pressure (IOP) is its only modifiable risk factor. The importance of robust lowering of IOP for prevention of glaucoma onset and progression is well established. Although IOP is a dynamic parameter with individual circadian rhythms, current management usually relies on single IOP measurements during regular clinic hours performed a few times a year. Recent technological advances have provided clinicians with tools for continuous IOP monitoring during a 24 hour period in an ambulatory setting. There are two approaches being investigated. The first is permanent IOP monitoring through an implantable sensor and the other is temporary monitoring through a contact lens sensor. In this article, we discuss the shortcomings of the current gold standard for tonometry (Goldmann Applanation Tonometry) and the current experience with the first commercially available continuous 24 hour IOP monitoring technology (SENSIMED Triggerfish®); a telemetric contact lens sensor produced by a Swiss start-up company (Sensimed AG, Lausanne, Switzerland). Recent studies suggest that 24 hour continuous monitoring of IOP can be integrated into clinical practice and have the potential to contribute to the reduction of glaucoma-related vision loss.